PENGARUH LATIHAN KNEE-TUCK JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLAVOLI PUTRA MADRASAH ALIYAH AL-HIDAYAH BANTAN KABUPATEN BENGKALIS - M. Arif Rahman; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is when a player or a smasher is practicing a smash with a smash technique that is incorrect but there are a lot of balls that concern the net. The title in this study is "the effect of knee-tuck jump training on leg muscle power on the men's volleyball team of Ma Al-Hidayah Bantan District of Bengkalis" so that the future goal of athletes can perform and play much better. The form of this research is (one group pretest-posttest design) with a population of men's volleyball team Madrsah Aliyah Al-Hidayah Bantan, Bengkalis Regency. The data in this study are the entire population of 10 people. The instrument used in this research was to use a vertical power jump test, which aims to find out how much influence the athlete's leg muscle power. to test normality using the lilifours test at a significance level of 0.05α. Based on the analysis of normality test data X produces a Lcount of 0.147 and a Ltable of 0.258, meaning that Lcount <Ltable. while the Y variable yields Lhitung of 0.141 and Ltable of 0.258. This means Lcount <LTabel. then the data is normally distributed. Thus it can be concluded that for the effect of the variable x with the variable y obtained the value of t = 3.136 then tcount> ttable ((3.136)> (1.833), then Ha is accepted, in other words there is a significant effect on the effect of knee-tuck jump exercises on power limb muscle Men's volleyball athlete Madrsah Aliyah Al-Hidayah Bantan Bengkalis Regency.Key Words: Knee Tuck Jump Exercise, Leg Muscle Power